A comparative study of phytotoxic effects of metal oxide (CuO, ZnO and NiO) nanoparticles on in-vitro grown Abelmoschus esculentus. (13th January 2021) - Baskar, Venkidasamy; Safia, Nayeem; Sree Preethy, Kuppuraj; Dhivya, Selvaraj; Thiruvengadam, Muthu; Sathishkumar, Ramalingam
Abstract: The extensive use of nanoparticles (NPs) in various industrial and household products pose a threat of their release into the environment. Plants being sessile are prone to be directly affected by these nanomaterials in polluted soils, which may represent possible risks to food safety and human health. In the present study, we compared the phytotoxic effects of metal oxide NPs namely nickel oxide (NiO), copper oxide (CuO) and zinc oxide (ZnO) NPs at four varying concentrations (100, 250, 500 and 1000 mg/L) on in-vitro grown seedlings of Abelmoschus esculentus (okra). All the NPs tested demonstrated a suppressed plant growth in a concentration-dependent manner which was evidenced from the repression of shoot and root length. A decrease in chlorophyll content was recorded in the NP-treated plants. Anthocyanin contents, total phenolic and total flavonoid contents were significantly altered in the NP-treated plants. Moreover, reactive oxygen species (ROS) generation was monitored in the roots of NP-treated plants using 4-nitro blue tetrazolium chloride (NBT) and 3, 3′-diaminobenzidine (DAB) staining, demonstrated an increase in ROS production in a dose-dependent manner in plants exposed to all three NPs. Enhanced ROS and malondialdehyde (MDA) production was recorded in A. esculentus seedlings when exposed to NPs. Among the three metal oxide NPs compared in the study, NiO NPs were found to be more toxic than CuO and ZnO ones.